Optimization of Library Service Management in Increasing Students' Reading Interest: Case Study at MI Muhammadiyah Paremono - Nugroho, Irham; Pratiwi, Eko Kurniasih; Isnaini, Rizki Shofak; Mareza, Lia; Sulimah, Sulimah (Universitas Muhammadiyah Purwokerto, 2024)
School libraries play a crucial role in supporting the learning process and increasing students' reading interest, but in MI Muhammadiyah Paremono, library management is not optimal. This study aims to evaluate the effectiveness of library management training for teachers in improving knowledge, skills, and its impact on students' reading interest. Using a one group pre-test post-test research design, the subjects of the study consisted of 21 teachers who were given a Likert scale questionnaire before and after the training. The results of the analysis showed a significant increase in pre-test and post-test scores for knowledge (from 3.2 to 4.5), skills (from 3.1 to 4.4), and perceptions of students' reading interest (from 3.0 to 4.2), with p < 0.01. This training successfully improved teachers' competence in library management, which had positive implications for students' reading interest. This study underlines the importance of library management training for teachers to improve students' learning experiences and encourage a reading culture in schools. These findings provide significant contributions to the development of teaching methods and library management, as well as opening up opportunities for further research on the factors that influence students' reading interest.